The making of the Cold War enemy : culture and politics in the military-intellectual complex - Robin, Ron Theodore (Princeton University Press, 2003)
At the height of the Cold War, the U.S. government enlisted the aid of a select group of psychologists, sociologists, and political scientists to blueprint enemy behavior. Not only did these academics bring sophisticated concepts to what became a project of demonizing communist societies, but they influenced decision-making in the map rooms, prison camps, and battlefields of the Korean War and in Vietnam. With verve and insight, Ron Robin tells the intriguing story of the rise of behavioral scientists in government and how their potentially dangerous, "American" assumptions about human behavio